Assessing vaccine data recording in Brazil - Mario Lucio de Oliveira Novaes; Renan Moritz Varnier Rodrigues de Almeida; Ronaldo Rocha Bastos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACT: Objectives: Vaccines represent an important advancement for improving the general health of a population. The effective recording of vaccine data is a factor for the definition of its supply chain. This study investigated vaccine data recording relatively to data collected from vaccination rooms and data obtained from a government-developed Internet platform. Methods: The monthly recorded total number of diphtheria and tetanus toxoids and pertussis vaccine (alone or in combination with the Haemophilus influenzae type b conjugate vaccine) doses administered in a medium-sized city of the Southeast region of Brazil was collected for the period January/2006 through December/2010 from two sources: City level (directly from vaccination rooms, the study "gold standard"), and Federal level (from an Internet platform developed by the country government). Data from these sources were compared using descriptive statistics and the Percentage error. Results: The data values made available by the Internet platform differed from those obtained from the vaccination rooms, with a Percentage error relatively to the actual values in the range [-0.48; 0.39]. Concordant values were observed only in one among the sixty analyzed months (1.66%). Conclusions: A frequent and large difference between the number of diphtheria and tetanus toxoids and pertussis vaccine doses administered in the two levels was detected.